2018
DOI: 10.1159/000485890
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Modulate Th1 and Th2 Responses in Asthmatic Mouse Models by Inhibition of Notch1 Signaling

Abstract: Background: Notch1 has been linked to the pathogenesis of asthma due to its contribution on Th1/Th2 imbalance. γ-Secretase inhibitor (GSI) acts as an effective blocker of Notch1 signaling. Glucocorticoids (GCs) are the most effective anti-inflammatory drugs for asthma. The present study investigated the involvement of the Notch1 pathway in the anti-inflammatory effect of GCs and its association with Th1/Th2 balance. Methods: The asthma model was established in BALB/c mice by sensitization with ovalbumin (OVA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Increasing evidence has indicated that the incidence and mortality rates of asthma have markedly increased worldwide. It has been reported that glucocorticoid drugs exhibit protective effects on airway remodeling and inflammation in a mouse asthma model [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that the incidence and mortality rates of asthma have markedly increased worldwide. It has been reported that glucocorticoid drugs exhibit protective effects on airway remodeling and inflammation in a mouse asthma model [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [26] investigated the role of Notch1 signaling as well as therapeutic capabilities of a γ-secretase inhibitor (GSI), which inhibits Notch 1. Notch 1 is thought to contribute to the development of asthma by contributing to the Th1/Th2 disbalance [27].…”
Section: Asthmamentioning
confidence: 99%
“…DEX and/or GSI treatment reduced the expression of the Notch1/NICD1 pathway in the lung, particularly in CD4 + T cells. Evidence of the upregulation of Th1/Th2 ratios in lung tissues, via a reduction in GATA3 and an increase in T-bet, was observed [26]. …”
Section: Asthmamentioning
confidence: 99%
“…The Notch signaling pathway is a highly evolutionarily conserved cell signaling pathway in most multicellular organisms that regulates proliferation, differentiation, cell fate, progenitor, and stem-cell self-renewal in both embryonic and adult tissues. Reports indicate that it is involved in AHR [9]. Several studies have demonstrated that BECs can express all the ligands of Notch-1, which is correlated with the differentiation of Th lymphocytes [10].…”
Section: Introductionmentioning
confidence: 99%